A Rare Case of Obstructive Shock due to Cardiac Tamponade in a Term Pregnancy - Masten, Megan; Kaliounji, Haya; Chou, Josephine; Tumolo, Alexis; Hirshberg, Jonathan S.; Sayres, Lauren (American Journal of Perinatology Reports, 2023)
Obstructive shock due to cardiac tamponade is a rare, life-threatening occurrence in the peripartum period. Etiologies include preeclampsia, infection, autoimmune conditions, and malignancy. Early recognition of the underlying disease process allows for multidisciplinary treatment and a favorable outcome.A 33-year-old presented for cardiac tamponade identified in the peripartum period. She was diagnosed with preeclampsia with severe features immediately prior to her repeat cesarean delivery and received magnesium prophylaxis. Postoperatively, she developed hypotension, tachycardia, and shortness of breath and was found to have a pericardial effusion with tamponade physiology. She underwent pericardial drain placement which was initially successful. However, she had recurrent symptomatic tamponade and thus a pericardial window was performed resulting in improvement of her symptoms. Workup revealed pericardial inflammation possibly secondary to a viral source, and she was successfully treated with anti-inflammatory therapy.We hypothesize that this patient's cardiac tamponade was caused by inflammatory pericarditis exacerbated by severe preeclampsia. Preeclampsia is a disease characterized by cardiovascular remodeling and fluid shifts in other compartments and thus is theorized to have contributed to this patient's effusion. Cardiac tamponade should be considered in the differential for any parturient presenting with hypotension and shortness of breath.
Keywords: cardiac tamponade; pericardial effusion; pericarditis; obstructive shock; preeclampsia